Defining risk acceptance criteria in occupational settings: A case study in the furniture industrial sector. (December 2015) - Rodrigues, Matilde A.; Arezes, Pedro M.; Leão, Celina P.
Highlights: The problem of the definition of the acceptance criteria for occupational settings is analysed. Acceptance criteria were defined for a case study on the furniture industrial sector. The integration of the acceptance criteria in a risk matrix is demonstrated. Abstract: The use of appropriate acceptance criteria in the risk assessment process for occupational accidents is an important issue but often overlooked in the literature, particularly when new risk assessment methods are proposed and discussed. In most cases, there is no information on how or by whom they were defined, or even how companies can adapt them to their own circumstances. Bearing this in mind, this study analysed the problem of the definition of risk acceptance criteria for occupational settings, defining the quantitative acceptance criteria for the specific case study of the Portuguese furniture industrial sector. The key steps to be considered in formulating acceptance criteria were analysed in the literature review. By applying the identified steps, the acceptance criteria for the furniture industrial sector were then defined. The Cumulative Distribution Function (CDF) for the injury statistics of the industrial sector was identified as the maximum tolerable risk level. The acceptable threshold was defined by adjusting the CDF to the Occupational, Safety & Health (OSH) practitioners' risk acceptance judgement. Adjustments of acceptance criteria to the companies' safety cultures were exemplified by adjusting the Burr distribution parameters. An example of a risk matrix was also used to demonstrate the integration of the defined acceptance criteria into a risk metric. This work has provided substantial contributions to the issue of acceptance criteria for occupational accidents, which may be useful in overcoming the practical difficulties faced by authorities, companies and experts.